2017
DOI: 10.1002/ldr.2674
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Point Measurement of Near‐surface Saturated Soil Hydraulic Conductivity in a Small Sicilian Basin

Abstract: Hydraulic conductivity of saturated soil, Ks, controls many hydrological processes. Parameterization of basin hydrological models in terms of Ks is complicated and uncertain owing to the very high spatial variability of this soil property. A small Sicilian basin was intensively sampled by the simplified falling head technique to obtain spatially distributed Ks data, and an attempt to explain their spatial variability on the basis of soil physical characteristics, digital elevation model‐derived topographic att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 94 publications
(147 reference statements)
0
12
0
1
Order By: Relevance
“…The parametric equations described by Liu et al [61] are used to calculate CR and DP. The water balance is highly affected by runoff, RO, [62], which in turn is highly influenced by the soil's hydrological characteristics [63,64]. AQUACROP estimates RO by using the curve number approach [65], and splits the maximum ET component, ET c , in maximum soil evaporation, E s (mm), and maximum crop transpiration, T c (mm), which are estimated as:…”
Section: Model Descriptionmentioning
confidence: 99%
“…The parametric equations described by Liu et al [61] are used to calculate CR and DP. The water balance is highly affected by runoff, RO, [62], which in turn is highly influenced by the soil's hydrological characteristics [63,64]. AQUACROP estimates RO by using the curve number approach [65], and splits the maximum ET component, ET c , in maximum soil evaporation, E s (mm), and maximum crop transpiration, T c (mm), which are estimated as:…”
Section: Model Descriptionmentioning
confidence: 99%
“…It should be observed that the latter option differs from the usual logical hydraulic design sequence, where first the emitter's flow rate is fixed, and then the inside lateral diameter is calculated. In fact, the emitter's flow rate is usually determined in the previous agronomic design, according to the wetted soil volume, the root length and the soil's hydrological characteristics that may be highly spatially variable, even in small cultivated areas (Baiamonte et al, ).…”
Section: Deriving Analytical Solution Accounting For Minor Lossesmentioning
confidence: 99%
“…Saturated soil hydraulic conductivity (K Sat ) is a key soil attribute for understanding the soil water movement phenomenon and is therefore one of the main inputs used in hydrological models. Several studies have reported that K Sat values are affected by the variation of pore space geometry (Baiamonte et al 2017), topography (Wang et al 2013), land use (Price et al 2010;Salemi et al 2013;Pinto et al 2019), and scale (Picciafuoco et al 2019). It has also been well documented in the literature that K sat is highly variable in space (Wang et al 2013;Papanicolaou et al 2015;She et al 2017).…”
Section: Introductionmentioning
confidence: 95%